Report of the Japanese Summer Parties in Dry Valleys, Victoria Land IX. A Preliminary Report of the Geophysical Study of Dry Valleys in 1970-1971 (Reports of the Japanese Antarctic Research Expedition) - Yoshio YOSHIDA; Yuki YUSA; Kiichi MORIWAKI; Tetsuya TORII (National Institute of Polar Research, 1971)
The geophysical study of Lake Vanda in the Dry Valley, Victoria Land, was carried out by the Japanese party in the austral summer of 1970-71. The work was supported by the Ministry of Education and the Science Council of Japan. It was conducted as a part of the New Zealand Antarctic Research Programme. The study was focussed mainly on the heat balance of Lake Vanda. Geochemical and geomorphological studies were carried out so far as the physical environment of the lake is concerned. Items, methods and instruments of the observations, and some results are briefly described. Items of the observations are as follows : (1) Change of lake level. (2) Vertical and horizontal distributions of water temperature and electric conductivity, and their seasonal changes. (3) Continuous measurement of water temperature at one station. (4) Thickness of lake ice and its change. (5) Temperature profile of lake ice and its change. (6) Temperature profiles of bottom sediments. (7) Evaporation from water surface and sublimation from ice surface. (8) Intensity of solar radiation under lake ice (measurement of ratio of solar radiation under lake ice to total incoming radiation). (9) Short period fluctuations of lake level (seiche). (10) Water temperature of inflow from the Onyx River. (11) Vertical distribution of water temperature and electric conductivity in Lake Bonney. (12) Vertical distribution of dissolved oxygen, pH, alkalinity and hydrogen sulfide in the lake, and sampling of water for other chemical analysis. (13) Sampling of semifossilized algae. (14) Sampling of water from the Onyx River, ohter small streams and pools. (15) Sampling of bottom sediments. (16) Sampling of glacier ice. (17) Sounding of the lake. (18) Meteorological observation. (19) Geomorphological survey.